2005
DOI: 10.1007/bf02978210
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin induces growth arrest and apoptosis of MDA-MB-231 breast cancer cell

Abstract: Recently, it was reported that reduction in serum adiponectin levels is correlated with the incidence of breast cancer. As an effort to explain this, we screened various human breast cancer cell lines to identify those in which proliferation is directly controlled by adiponectin. Among the five tested cell lines, proliferation of MDA-MB-231 cancer cell was significantly suppressed by adiponectin within the range of physiological concentration. Furthermore, prolonged adiponectin treatment caused cell growth arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
111
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(124 citation statements)
references
References 25 publications
9
111
1
3
Order By: Relevance
“…Several groups reported previously that MDA-MB-231 cells were growth inhibited by Acrp30 (Kang et al, 2005;Wang et al, 2007). However, in our hands proliferation of this cell line was not statistically inhibited by the addition of Acrp30.…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…Several groups reported previously that MDA-MB-231 cells were growth inhibited by Acrp30 (Kang et al, 2005;Wang et al, 2007). However, in our hands proliferation of this cell line was not statistically inhibited by the addition of Acrp30.…”
Section: Discussioncontrasting
confidence: 78%
“…This was suggested by the increase in cleaved caspase-8 and cleaved PARP in these cells. Other reports have found that apoptosis is involved in growth inhibition by Acrp30 by the use of TUNEL or annexin V assays (Kang et al, 2005;Dieudonne et al, 2006;Wang et al, 2006). We have extended those earlier observations by identifying increased cleavage of caspase-8 and PARP following treatment with Acrp30.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations